Bacillus cereus efflux protein BC3310 - a multidrug transporter of the unknown major facilitator family, UMF-2 - Kroeger, Jasmin K.; Hassan, Karl; Vörös, Aniko; Simm, Roger; Saidijam, Massoud; Bettaney, Kim E.; Bechthold, Andreas; Paulsen, Ian T.; Henderson, Peter; Kolstø, Anne-Brit (Frontiers in Microbiology, 2015)
Phylogenetic classification divides the major facilitator superfamily (MFS) into 82 families, including 25 families that are comprised of transporters with no characterized functions. This study describes functional data for BC3310 from Bacillus cereus ATCC 14579, a member of the “unknown major facilitator family 2” (UMF 2). BC3310 was shown to be a multidrug efflux pump conferring resistance to ethidium bromide, SDS and silver nitrate when heterologously expressed in E. coli DH5α ΔacrAB. A conserved aspartate residue (D105) in putative transmembrane helix 4 was identified, which was essential for the energy dependent ethidium bromide efflux by BC3310. Transport proteins of the MFS comprise specific sequence motifs. Sequence analysis of UMF 2 proteins revealed that they carry a variant of the MFS motif A, which may be used as a marker to distinguish easily between this family and other MFS proteins. Genes orthologous to bc3310 are highly conserved within the B. cereus group of organisms and thus belong to the core genome, suggesting an important conserved functional role in the normal physiology of these bacteria.